The “Peculiar Light” of Blakean Vision: Reorganizing Enlightenment Discourse and Opening the Exemptive Sublime - Chernik, Aria (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis article argues that there is a direct connection between Blake’s rejection of conventional Enlightenment aesthetics—namely, of tropes pertaining to light and darkness and void and chaos—and a space of liberty that is opened for the reader. This space, which I term the “exemptive sublime,” is free from interpretive mandates and even orthodox assumptions. To illustrate the affiliation between Blake’s radical aesthetics and the radical space of liberty that is created for the reader, I first briefly consider how even in some of his earliest works, such as “The Little Black Boy” and The Marriage of Heaven and Hell, Blake is already complicating notions of light, darkness, and void. I then turn my analysis to the verbal and visual designs of the opening plates in The [First] Book ofUrizen to demonstrate how Blake boldly reorganizes Enlightenment epistemological and ontological discourse so that places of void and darkness become places of productive insight. In its characteristic emphasis on the importance of inspired Vision over empirical sight, Blake’s composite art opens not just a space of liberty in which to question hegemonic doctrine, but also a space for ethical reflection.